Structural patterns o f lexical bundles in business studies research articles - Pathmanathan, Shamila; Paramasivam, Shamala; Mohamad Ali, Afida; Haji Darmi, Ramiza (Macrothink Institute, Inc., 2024)
Lexical bundles are defined as sequences of words that frequently occur together in a register. They are regarded as essential components of written academic discourse as they are prevalent in written registers. The purpose of this study is to examine the structure of three-to-six-word lexical bundles identified in the three sections of the business studies research articles: the Introduction, the Method and the Results sections, and classify them into structural categories. Subsequently, these bundles are compared across the three sections of the business studies research articles in terms of their structural patterns. A corpus-based approach was adopted in order to identify the lexical bundles. AntConc 3.5.8w (Anthony, 2019) computer software was used to generate the lexical bundles from the research articles. The findings revealed that there are structural differences in the use of lexical bundles across the three sections, and that most of the lexical bundles constituted noun phrases and prepositional phrases. The findings also show that business academic writers rely most on noun phrases and phrasal bundles for producing their written discourse. In this study, a list of lexical bundles in business studies research publications from various business subject areas, along with the structure of these bundles, is an outcome of the study that would be of significance to academic writers in the field of business studies. The results of this study have pedagogical implications for EAP course developers and instructors.